Political Opinion and the Trends in Romanian Government Expenditures - Cosmin Gabriel MARIAN; Ronald F. King (Transylvanian Review of Administrative Sciences, 2016)
A critical question for citizen deliberation is whether the country expends the right amount of public funds, allocated in the right proportions across the various substantive tasks of the government. Romania shows clear linear expenditure trends over time, largely independent of the government or political party in power. The Median Voter Theorem suggests that this might be an anticipated and legitimate democratic outcome given the incentive for politicians to follow movements in majority opinion or else risk electoral defeat. Yet the theorem, we discover, does not succeed in explaining the direction of Romanian budget trends. This paper examines post-revolution Romanian national government expenditures, compared to the preferences expressed by Romanian citizens as best we can determine from available public opinion polls. The finding, despite limited data, is that government spending and popular preferences show little correspondence, indicating possible problems regarding democratic responsiveness.